2011
DOI: 10.5888/pcd9.110081
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Disseminating Evidence-Based Health Promotion Practices

Abstract: Wider adoption of evidence-based, health promotion practices depends on developing and testing effective dissemination approaches. To assist in developing these approaches, we created a practical framework drawn from the literature on dissemination and our experiences disseminating evidence-based practices. The main elements of our framework are 1) a close partnership between researchers and a disseminating organization that takes ownership of the dissemination process and 2) use of social marketing principles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 16 publications
1
70
0
4
Order By: Relevance
“…Although these advantages can help smaller workplaces implement health-promotion programs, they are often countered by the challenges described below. We draw from dissemination and implementation science frameworks to explore why smaller workplaces generally offer less health promotion than do larger workplaces (28,33,78). To capture the challenges smaller workplaces face, we use three framework elements: context, readiness, and capacity.…”
Section: Advantages and Challenges Smaller Workplaces Face In Workplamentioning
confidence: 99%
“…Although these advantages can help smaller workplaces implement health-promotion programs, they are often countered by the challenges described below. We draw from dissemination and implementation science frameworks to explore why smaller workplaces generally offer less health promotion than do larger workplaces (28,33,78). To capture the challenges smaller workplaces face, we use three framework elements: context, readiness, and capacity.…”
Section: Advantages and Challenges Smaller Workplaces Face In Workplamentioning
confidence: 99%
“…Cooperation and support from policy makers and management is attainable when it is demonstrated that NP addresses local healthcare and nursing predicaments for public good (Box 5a). Yura and Walsh [37] recommended the need to work with authorities; Haris et al [74] emphasized it; and both Ryan [12] practically demonstrates it.…”
Section: Resultsmentioning
confidence: 99%
“…Second, nurse educators working with nurses at policy level agreed to include Nursing Process as a major determinant in nursing promotions. Third, the use of Harris et al's [74] knowledge dissemination framework ensures that knowledge creators (nurse educators/researchers) and users (nurse policy makers and clinical practitioners) work together as change agents to ensure implementation.…”
Section: Way Forwardmentioning
confidence: 99%
“…Instead of researchers designing and implementing the dissemination activities, as is commonly the case (Bull et al, 2003), it was conducted in an applied setting in "a close partnership between researchers and a disseminating organization that takes ownership of the dissemination process" (Harris et al, 2012). It therefore examines dissemination strategies under real-life consulting conditions.…”
Section: Discussionmentioning
confidence: 99%